PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING BERBANTUAN MEDIA CANVA TERHADAP KETERAMPILAN MENULIS KALIMAT SEDERHANA SISWA SEKOLAH DASAR - Neng Putri Rakasiwi; Fitri Nuraeni; Nadia Tiara Antik Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of the research was caused by the low level of students' simple sentence writing skills due to the use of less diverse learning models and media. The objectives of the study were 1) to determine the effect of the snowball throwing type cooperative learning model assisted by Canva media on students' simple sentence writing skills; 2) to determine the effect of the STAD type cooperative learning model assisted by learning videos on students' simple sentence writing skills; and 3) to compare the increase in simple sentence writing skills of students who received the snowball throwing type cooperative learning model assisted by Canva media with students who received the STAD type cooperative learning model assisted by learning videos. Students in class II B as the experimental class used the snowball throwing type cooperative model assisted by Canva media and the control class used the STAD type cooperative model assisted by learning videos, namely class II D was the sample in the study consisting of 25 students. The simple sentence writing skill test instrument and observation sheets were used in this study. The results obtained showed 1) there was an effect of the snowball throwing type cooperative model assisted by Canva media on students' simple sentence writing skills by 53%; 2) there is an influence of the STAD type cooperative model on students' simple sentence writing skills by 37.3%; and 3) the increase in students' simple sentence writing skills using the snowball throwing type cooperative learning model assisted by Canva media is better than students who receive the STAD type cooperative learning model assisted by learning videos. It is recommended that teachers consider implementing this model as a writing teaching strategy with a more imaginative and modern approach.